2018
DOI: 10.21082/btsm.v9n1.2017.15-22
|View full text |Cite
|
Sign up to set email alerts
|

Keragaan Karakter Morfologi, Stomata, dan Klorofil Enam Varietas Tembakau Lokal Tulungagung

Abstract: <p>Tembakau lokal tulungagung merupakan salah satu jenis tembakau yang  memiliki peran penting dalam industri rokok kretek di Indonesia. Beberapa varietas tembakau telah banyak dibudidayakan di wilayah Kabupaten Tulungagung, tetapi tingkat heterogenitas tanaman cukup tinggi, baik secara morfologi maupun anatomi. Stomata merupakan salah satu bagian struktur daun yang sering digunakan dalam klasifikasi taksonomi sehingga informasi keragaman sifat morfologi, stomata dan kadar klorofil dapat dimanfaatkan pem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
0
3
0
4
Order By: Relevance
“…The analysis results show that the structure of the tobacco leaf has similarities with the shape of the Gunungan Wayang Purwa, where the shape of the tobacco leaf is generally oval-shaped, the tip is tapered and is getting thinner. This result is reinforced by the research of Rochman & Hamida (2018), which examined six varieties of tobacco leaves and displayed the shape and characteristics of tobacco leaves. This study includes a philosophical element of the no-smoking rule in developing wayang designs.…”
Section: Tobacco Leaf Structure Analysismentioning
confidence: 95%
“…The analysis results show that the structure of the tobacco leaf has similarities with the shape of the Gunungan Wayang Purwa, where the shape of the tobacco leaf is generally oval-shaped, the tip is tapered and is getting thinner. This result is reinforced by the research of Rochman & Hamida (2018), which examined six varieties of tobacco leaves and displayed the shape and characteristics of tobacco leaves. This study includes a philosophical element of the no-smoking rule in developing wayang designs.…”
Section: Tobacco Leaf Structure Analysismentioning
confidence: 95%
“…A high stomatal distribution ratio indicates a greater number of stomata in a certain area and it will help to increase the rate of transpiration. According to Rehfeldt, Wykoff, & Ying [34] a high stomatal distribution ratio indicates the ability of plants to adapt to a drought-prone environment. Red Shoots (Syzygium paniculatum Gaertn) is a plant that is usually used as an ornamental plant as well as shade plants.…”
Section: The Ratio Of Stomatal Distributionmentioning
confidence: 99%
“…According to Judge, Dorly, & Rahayu [16], the distribution of stomata which is the ratio of the number of stomata or epidermal cells in a certain area unit will change if plants are planted in different environments. Rochman & Hamida [34] showed that the distribution of stomata decreased or increased when plants were planted under certain conditions. Stomata are holes or gaps in the leaf epidermis that are limited by 2 guard cells that function to enter and exit gases, including water vapor [35].…”
Section: Introductionmentioning
confidence: 99%
“…Kadar klorofil akan berpengaruh langsung terhadap fotosintesis yang akhirnya akan berpengaruh terhadap pertumbuhan dan hasil (Nurnasari and Djumali, 2012). Hasil penelitian Rochman and Hamida, (2017), juga menyebutkan bahwa luasan daun berhubungan dengan peningkatan kandungan klorofil yang akan berdampak terhadap bertambahnya produk fotosintesis dan meningkatkan laju pertumbuhan dan produksi tanaman.…”
Section: Hasil Dan Pembahasan Hasil Penelitianunclassified
“…Hasil pengukuran kadar klorofil ini mendukung peningkatan produktivitas tanaman. Semakin tinggi kadar klorofil daunnya maka produktivitas dan indeks tanamannya juga semakin tinggi (Rochman & Hamida, 2017), sedangkan kandungan klorofil berpengaruh langsung terhadap fotosintesis yang akhirnya akan berpengaruh terhadap pertumbuhan dan hasil (Djumali and Nurnasari, 2012).…”
Section: Pembahasanunclassified